2013
DOI: 10.1002/ajhb.22356
|View full text |Cite
|
Sign up to set email alerts
|

A Half Century of High‐Altitude Studies in Anthropology: Introduction to the Plenary Session

Abstract: Until 50 years ago, high-altitude terrestrial research was conducted largely within the realm of environmental physiology, where interests were focused on physiological mechanisms and mountain exploration. Scientists from the United States, Europe, and Peru had developed sophisticated physiological models of adaptation and acclimatization to the hypoxia of high altitude, but very little research had been conducted on permanent residents, particularly natives of high altitude in the two major regions of the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition, the shift from the early research designs that emphasized single population studies to those that focus on comparing adaptive patterns across populations, has allowed us to better understand the influence of natural selection on human variation. This has been particularly evident in high altitude research, where studies of indigenous highland populations of Tibet and Ethiopia clearly show striking differences in adaptive physiology and morphology from the classic “Andean” pattern documented by the IBP‐HAP studies (see Beall, ; Little, Thomas, & Garruto, , and Section 5.3). As such we are now gaining a much richer picture of how physiological acclimatization and natural selection interact to produce variation in adaptive responses to similar stressors in different populations.…”
Section: Human Adaptability and The International Biological Programmmentioning
confidence: 94%
“…In addition, the shift from the early research designs that emphasized single population studies to those that focus on comparing adaptive patterns across populations, has allowed us to better understand the influence of natural selection on human variation. This has been particularly evident in high altitude research, where studies of indigenous highland populations of Tibet and Ethiopia clearly show striking differences in adaptive physiology and morphology from the classic “Andean” pattern documented by the IBP‐HAP studies (see Beall, ; Little, Thomas, & Garruto, , and Section 5.3). As such we are now gaining a much richer picture of how physiological acclimatization and natural selection interact to produce variation in adaptive responses to similar stressors in different populations.…”
Section: Human Adaptability and The International Biological Programmmentioning
confidence: 94%
“…The development and impact of the biocultural and genetic/adaptive research domains have been particularly evident in high‐altitude research (Beall, 2013; Little et al, 2013). The original IBP high altitude research in the Andes found no evidence for genetic adaptations to altitude stress among the Quechua (Baker & Little, 1976).…”
Section: High Altitude Adaptation: Evolutionary and Biocultural Dimen...mentioning
confidence: 99%
“…Populations living at HA experience pervasive and ever‐present stressors (e.g., hypoxia) that are not easily modified by cultural or behavioral responses (Beall, ; Frisancho, ). The study of these populations has long served as a foundational paradigm in biological anthropology, representing a robust model to not only study genetic adaptation, but also the role of phenotypic plasticity under extreme environmental stress (Frisancho, ; Little, Thomas, & Garruto, ).…”
mentioning
confidence: 99%